Sustainable Engineering and Agro-Food Processing : Renewable and Nonrenewable Resources - Buenrostro-Figueroa, José Juan, 1985- (Apple Academic Press, 2025)
This new book focuses on the challenges of implementing sustainability in different contexts of biodiversity and ecosystems for shaping the future of engineering in the agro-food processing industry and addresses sustainable applications of renewable and nonrenewable resources. It highlights the engineering advancements and processing solutions for agricultural and food engineering and discusses the handling of agro-industrial waste and biorefineries, developing bioactive compounds from agro-industrial waste, using sustainable technologies for resource recovery from waste, employing spray drying in food processing, developing healthy and sustainable replacements for saturated and hydrogenated fats, and creating and enhancing healthy foods for the future.